PENGARUH PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL PADA INTERVENING CV. RUMAH WARNA YOGYAKARTA - risty yulita pramesty (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe the development of career influence on employee job satisfaction in CV. Rumah Warna Yogyakarta, work motivation as intervening variable has an effect on career development towards job satisfaction in CV. Rumah Warna Yogyakarta. This type of research is quantitative research. The population is 85 employees CV. Rumah Warna Yogyakarta. The samples counted 85 respondents and used the saturated sampling technique. Methods of data collection were conducted with questionnaire media, while data analysis techniques used simple linear regression analysis and multiple linear regression analysis. The results showed that career development has an effect on employee job satisfaction in CV. Rumah Warna Yogyakarta β 0.621, work motivation as intervening variable affect career development towards job satisfaction in CV. Rumah Warna Yogyakarta β 0.651.